Raised within government walls: The early years of program evaluation in the US - Arthur Brackmann Netto (Duke University, Center for the History of Political Economy (CHOPE), 2021)
Not much equates Michael Harrington, Dwight MacDonald, Orley Ashenfelter and James Heckman. But still history made a way to have, in one end of a story, a narrative journalist and a political scientist and, in the other, two economists. Harrington's famous piece, The Other America, made its way into government through MacDonald's extensive review in what could have been just another edition of the New Yorker in that January of 1963. MacDonald's lines ended up in John Kennedy's hands - or so the tale tells - and poverty made its way inside governmental concerns. "Poverty knowledge", then, spin and turned for 15 years for in one of its ramifications to conceive the field of microeconometrics. Poverty went from a campaign theme to an unconditional war, from unmeasurable to fashionable. It travelled through the Council of Economic Advisers and the Office of Economic Opportunity, to the Department of Labor and teaching rooms of universities. It finally reached the Office of the Assistant Secretary for Policy, Evaluation and Research (ASPER), where it became econometric policy evaluation and microeconometrics, embodied in the papers of Ashenfelter and Heckman in the late 70s. This paper intends to shed some light in this journey towards microeconometrics.
Keywords: 330